Comparing nSOFA, CRIB-II, and SNAPPE-II for predicting mortality and short-term morbidities in preterm infants ≤32 weeks gestation - Qingfei Hao; Jing Chen; Haoming Chen; Jing Zhang; Yanna Du; Xiuyong Cheng (Annals of Medicine)
Background Neonatal illness severity scores are not extensively studied for their ability to predict mortality or morbidity in preterm infants. The aim of this study was to compare the Neonatal Sequential Organ Failure Assessment (nSOFA), Clinical Risk Index for Babies-II (CRIB-II), and Score for Neonatal Acute Physiology with Perinatal extension-II (SNAPPE-II) for predicting mortality and short-term morbidities in preterm infants ≤32 weeks.Methods In this retrospective study, infants born in 2017–2018 with gestational age (GA) ≤32 weeks were evaluated. nSOFA, CRIB-II, and SNAPPE-II scores were calculated for each patient, and the ability of these scores to predict mortality and morbidities was compared. The morbidities were categorized as mod/sev bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC) requiring surgery, early-onset sepsis (EOS), late-onset sepsis (LOS), retinopathy of prematurity (ROP) requiring treatment, and severe intraventricular hemorrhage (IVH). Calculating the area under the curve (AUC) on receiver operating characteristic curves (ROC) analysis to predict and compare scoring systems’ accuracy.Results A total of 759 preterm infants were enrolled, of whom 88 deceased. The median nSOFA, CRIB-II, and SNAPPE-II scores were 2 (0, 3), 6 (4, 8), and 13 (5, 26), respectively. Compared with infants who survived, these three scores were significantly higher in those who deceased (p < 0.05). For predicting mortality, the AUC of the nSOFA, SNAPPE-II, and CRIB-II were 0.90, 0.82, and 0.79, respectively. The nSOFA scoring system had significantly higher AUC than CRIB-II and SNAPPE-II (p < 0.05). However, short-term morbidities were not strongly correlated with these three scoring systems.Conclusion In infants ≤32 weeks gestation, nSOFA scoring system is more valuable in predicting mortality than SNAPPE-II and CRIB-II. However, further studies are required to assess the predictive power of neonatal illness severity scores for morbidity.